2015
DOI: 10.1210/jc.2014-3339
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes, Myocardial Infarction and Stroke Are Distinct and Duration-Dependent Predictors of Subsequent Cardiovascular Events and All-Cause Mortality in Older Men

Abstract: In older men, increasing duration of diabetes predicts stable increases in all-cause and MI-related mortality and a progressively higher risk of stroke deaths. Prior MI was associated with increased risk of subsequent MI, and prior stroke with subsequent stroke, particularly in the 10-20 years following the first event. Diabetes is a duration-dependent risk factor for cardiovascular events which influences outcomes differently from prior vascular disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
1
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 48 publications
1
26
1
2
Order By: Relevance
“…Second, our study cohort was preselected for being otherwise healthy patients with T2DM without clinical CVD. Therefore, our results may not be applicable to the general population with diabetes, and we could not compare our findings with those of other population-based studies [38, 39]. Furthermore, the cohort consists of only Korean Asians and may not be representative of other Asians or other racial–ethnic minority groups; our findings should be interpreted with caution with respect to different racial–ethnic groups because the environmental and genetic factors may differ among various racial–ethnic groups, and there may be racial–ethnic differences in the prevalence of MACE in patients with T2DM.…”
Section: Discussionmentioning
confidence: 76%
“…Second, our study cohort was preselected for being otherwise healthy patients with T2DM without clinical CVD. Therefore, our results may not be applicable to the general population with diabetes, and we could not compare our findings with those of other population-based studies [38, 39]. Furthermore, the cohort consists of only Korean Asians and may not be representative of other Asians or other racial–ethnic minority groups; our findings should be interpreted with caution with respect to different racial–ethnic groups because the environmental and genetic factors may differ among various racial–ethnic groups, and there may be racial–ethnic differences in the prevalence of MACE in patients with T2DM.…”
Section: Discussionmentioning
confidence: 76%
“…It has been reported that the duration of diabetes is prospectively associated with the risk of diabetic micro‐ and macroangiopathies in both elderly and non‐elderly patients with type 2 diabetes, although there are no previous reports that investigated the relationship between the duration of diabetes and vascular complications in Japanese patients with type 2 diabetes . Yeap et al .…”
Section: Discussionmentioning
confidence: 99%
“…A study of nearly 12 000 community-dwelling men in western Australia found that diabetes mellitus significantly increased the risk of death in patients with stroke. 83 Moreover, the duration of diabetes mellitus was a significant cofactor, suggesting a dose-response relationship of diabetes mellitus exposure to stroke severity. These observations are similar to those reported in a German nationwide health insurance study 84 and a Veterans Affairs investigation.…”
Section: Strokementioning
confidence: 99%